Sexual Enhancement Products for Sale Online: Raising Awareness of the Psychoactive Effects of Yohimbine, Maca, Horny Goat Weed, and Ginkgo biloba. (15th June 2014) - Corazza, Ornella; Martinotti, Giovanni; Santacroce, Rita; Chillemi, Eleonora; Di Giannantonio, Massimo; Schifano, Fabrizio; Cellek, Selim
Abstract : Introduction . The use of unlicensed food and herbal supplements to enhance sexual functions is drastically increasing. This phenomenon, combined with the availability of these products over the Internet, represents a challenge from a clinical and a public health perspective. Methods . A comprehensive multilingual assessment of websites, drug fora, and other online resources was carried out between February and July 2013 with exploratory qualitative searches including 203 websites. Additional searches were conducted using the Global Public Health Intelligence Network (GPHIN). Once the active constitutes of the products were identified, a comprehensive literature search was carried out using PsycInfo and PubMed. Results . The most common sexual enhancement products available on the Internet were identified. Their active ingredients included yohimbine, maca, horny goat weed and Ginkgo biloba. These four substances were reported with the occurrence of adverse events and the induction of psychological symptoms, such as mood changes, anxiety, and hallucinations as well as addictive behaviours. Conclusions . Uncontrolled availability of sexual enhancement products that contain potentially harmful substances is a major public health concern. The possible impact on population health, particularly among subjects with psychiatric disorders, usually at risk for sexual dysfunction, may be significant. This new trend needs to be extensively studied and monitored.